2001
DOI: 10.1128/aem.67.4.1529-1535.2001
|View full text |Cite
|
Sign up to set email alerts
|

Cold-Adapted β-Galactosidase from the Antarctic Psychrophile Pseudoalteromonas haloplanktis

Abstract: The ␤-galactosidase from the Antarctic gram-negative bacterium Pseudoalteromonas haloplanktis TAE 79 was purified to homogeneity. The nucleotide sequence and the NH 2 -terminal amino acid sequence of the purified enzyme indicate that the ␤-galactosidase subunit is composed of 1,038 amino acids with a calculated M r of 118,068. This ␤-galactosidase shares structural properties with Escherichia coli ␤-galactosidase (comparable subunit mass, 51% amino sequence identity, conservation of amino acid residues involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
3
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(97 citation statements)
references
References 30 publications
3
90
3
1
Order By: Relevance
“…This provides only a small glimpse into the exceptional adaptation of the microbiota to the Antarctic environment. The Pseudoalteromonas isolates in particular showed great potential for bioprospecting of all screened enzymatic activities, a result that agrees with those from previous studies (Holmströ m & Kjelleberg 1999;Hoyoux et al 2001;Truong et al 2001;Tutino et al 2002;Zeng et al 2006). Beyond the biotechnological potential, the high proportion of isolates belonging to the genus Pseudoalteromonas and the versatile hydrolytic activities detected in this group also suggest that these organisms may play an important role in polymer hydrolysis in cold environments.…”
Section: Discussionsupporting
confidence: 80%
“…This provides only a small glimpse into the exceptional adaptation of the microbiota to the Antarctic environment. The Pseudoalteromonas isolates in particular showed great potential for bioprospecting of all screened enzymatic activities, a result that agrees with those from previous studies (Holmströ m & Kjelleberg 1999;Hoyoux et al 2001;Truong et al 2001;Tutino et al 2002;Zeng et al 2006). Beyond the biotechnological potential, the high proportion of isolates belonging to the genus Pseudoalteromonas and the versatile hydrolytic activities detected in this group also suggest that these organisms may play an important role in polymer hydrolysis in cold environments.…”
Section: Discussionsupporting
confidence: 80%
“…H-BgaS had a catalytic efficiency of 0.27 and 0.53 at 5 and 18°C, respectively. Both of these values are higher than those reported for a LacZ enzyme (0.15) without a His tag at 20°C (13).…”
Section: Comparison Of Bgas and Lacz Propertiescontrasting
confidence: 51%
“…To examine possible metal requirements for H-BgaS, it was treated with various concentrations of EDTA. Unlike the Pseudoalteromonas haloplanktis ␤-galactosidase, which was inhibited by 5 mM EDTA (13), no activity loss was detected until the EDTA concentration reached 100 mM, at which the enzyme was inactivated after a 1.5-h treatment. Activity of H-BgaS was relatively unchanged by the addition of Co 2ϩ , Cu 2ϩ , Ca 2ϩ , or Na ϩ (2, 2, 1.5, or 5% increase, respectively).…”
Section: Comparison Of Bgas and Lacz Propertiesmentioning
confidence: 99%
“…Even when some of the proteases from psychrotolerants had their maximal activity at similar temperatures than their corresponding mesophile, the majority of them showed curves of activity as a function of temperature shifted towards low temperatures, with apparent optimum values between 10 and 15 °C lower than Carlsberg Subtilisin. Other authors found similar results for proteases (Helmke & Weyland 1991;Turkiewicz et al 1999) and other enzymes Hoyoux et al 2001) produced by marine bacteria from permanently cold environments. This observation reveals a clear adaptation of the enzyme-producing strains to their habitats.…”
Section: Discussionsupporting
confidence: 70%